2019
DOI: 10.12659/msm.914295
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Induced Cancer Cell Senescence Shows a Time Delay Effect and Is Inhibited by Epithelial-Mesenchymal Transition (EMT)

Abstract: Background Senescence is a natural barrier for the body to resist the malignant transformation of its own cells. This work investigated the senescence characteristics of cancer cells in vitro . Material/Methods Human cervical cancer HeLa cells were treated with different concentrations of doxorubicin for 3 days, with or without subsequent extended culture in drug-free medium for 6 days. Senescent cell ratios between these 2 culture schemes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Although it has been shown that Doxo treatment can induce DNA damage and apoptosis in rapidly dividing cells in vivo and in vitro, the cellular response to Doxo can differ within a population of cells. Accordingly, a recent study demonstrated that proliferative epithelial cells either underwent apoptosis or became senescent, as confirmed by the expression of the characteristic SA marker and an increase in cell size [ 32 ]. Molecular mechanisms, which are involved in Doxo-induced senescence comprise p53 upregulation, oxidative stress, and concurrent caspase inhibition [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that Doxo treatment can induce DNA damage and apoptosis in rapidly dividing cells in vivo and in vitro, the cellular response to Doxo can differ within a population of cells. Accordingly, a recent study demonstrated that proliferative epithelial cells either underwent apoptosis or became senescent, as confirmed by the expression of the characteristic SA marker and an increase in cell size [ 32 ]. Molecular mechanisms, which are involved in Doxo-induced senescence comprise p53 upregulation, oxidative stress, and concurrent caspase inhibition [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…To overexpress Hif-2α in vitro, primary calvarial preosteoblasts were infected with adenovirus expressing Hif-2α at the indicated multiplicity of infection (MOI) on differentiation day 2. Doxorubicin is a commonly used chemotherapy drug that can induce DNA cross-linking and lead to cell apoptosis, autophagy, and/or senescence 28 . The concentration of doxorubicin used in this experiment did not cause cell apoptosis.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicate that DOC2B is associated with induction of senescence. Doxorubicin is well known inducer of senescence and is used as a positive control in senescence experiments (Hu and Zhang 2019;Saleh et al 2020).…”
Section: Doc2b Expression Induces Senescencementioning
confidence: 99%